Some histological aspects of the cervix during pregnancy - Gordillo Delboy, R. (2015)
It has been established in detail and precision histology I strain quadrant uterine pregnancy, childbirth and postpartum and significance of histological changes, if any, and particularly in relation to the carcinoma "in situ". We propose in this paper check some of these changes and the relationship can be saved in different periods of pregnancy.